Psiholoģiskās labklājības saistība ar apmierinātību ar partnerattiecībām - Balode, Inga (Latvijas Universitāte, 2016)
Šī pētījuma mērķis ir izpētīt, vai pastāv psiholoģiskās labklājības un apmierinātības ar partnerattiecībām atšķirības indivīdiem, kas atrodas reģistrētā laulībā, un, kas ir partnerattiecībās, bet neatrodas reģistrētā laulībā, un, vai pastāv atšķirības psiholoģiskās labklājības saistībā ar apmierinātību ar partnerattiecībām indivīdiem, kas atrodas reģistrētā laulībā, un, kas ir partnerattiecībās, bet nav reģistrētā laulībā. Pētījumā piedalījās 117 respondenti (90 sievietes, 27 vīrieši) vecumā no 20 līdz 77 gadiem (M = 38,94 gadi, SD = 12,27). 51 respondents norādīja, ka ir oficiāli nereģistrētās attiecībās (43,6%), 66 respondenti norādīja, ka ir oficiāli reģistrētās attiecībās (56,4%). Pētījumā tika izmantotas divas aptaujas. Psiholoģiskās labklājības izpētei tika izmantota Psiholoģiskās labklājības skala (Scales of Psychological Well-Being- RPWB, Ryff, 1989), kas adaptēta latviešu valodā (Voitkāne, Miezīte & Raščevska, 2004). Lai noteiktu dalībnieku apmierinātību ar partnerattiecībām, tika izmantota Apmierinātības ar partnerattiecībām aptauja (The Comprehensive Marital Satisfaction Scale – CMSS, Blum & Mehrabian, 1999). Metodes adaptāciju Latvijā veikusi Ilze Mizāne 2006. gadā. Pētījuma rezultāti apstiprināja, ka pastāv statistiski nozīmīgas atšķirības apmierinātībā ar attiecībām starp indivīdiem, kas atrodas reģistrētā laulībā, un, indivīdiem, kas ir partnerattiecībās, bet neatrodas reģistrētā laulībā. Apmierinātība ar partnerattiecībām laulātajiem ir augstāka, nekā indivīdiem nereģistrētās partnerattiecībās. Nepastāv statistiki nozīmīgas atšķirības psiholoģiskās labklājības un tās aspektu (sevis akceptēšana, tuvas attiecības ar citiem, autonomija, kompetence vides apguvē, dzīves mērķis un personības izaugsme) saistībā ar apmierinātību ar partnerattiecībām indivīdiem laulībā un indivīdiem, kas ir partnerattiecībās, bet nav reģistrētā laulībā. Indivīdi nereģistrētās partnerattiecībās uzrāda tikai tendenci saistībai starp apmierinātību ar attiecībām un psiholoģiskās labklājības apakšskalu – pozitīvas attiecības ar citiem

The purpose of the research was to clarify if there are any differences between the scores of psychological well-being and sastisfaction with partnership of individuals in officially registrated marriage and of those who are in partnership, but not in officially registrated marriage. Additionally clarification was made to state if there exist differences between psychological well-being in association with sastisfaction with partnership for both groups of research. The participants of the research were 117 respodents (90 women, 27 men) aging from 20 to 77 years (M = 38,94 years, SD = 12,28). 51 respondents pointed out, that they were in not officially registrated partnership (43,6 %), 66 respondents showed, that they were officially married (56,4 %). Participants filled out the following two kinds of self-reports. Scales of Psychological WellBeing – RPWB (Ryff, 1989), potted to Latvian condition, (Voitkāne, Miezīte & Raščevska, 2004) were used to identify participants’ psychological well-being. To identify participants satisfaction with their partnership The Comprehensive Marital Satisfaction Scale – CMSS (Blum & Mehrabian, 1999) was made use of. Ilze Mizāne potted this research to Latvian conditions in 2006. The results of the research approved, that there exists statistically significant differences in satisfaction with partnership among individuals in officially registrated marriage and of those who are in partnership, but not in officially registrated marriage. Satisfaction with partnership among the married ones scored higher than among individuals in not registrated partnership. Do not exist statistically significant differences between psychological well-being and its aspects (self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, personal growth) in association with sastisfaction with partnership for individuals in officially registrated marriage and of those who are in partnership, but not in officially registrated marriage. Individuls in not registrated partnership depicted only the tendency in association between satisfaction with partnership and the subscale of psychological well-being - positive relations with others
Psychological well-being in association with satisfaction with the partnership
Keywords: Psiholoģija; psiholoģiskā labklājība; apmierinātība ar partnerattiecībām; apmierinātība ar laulībām; psychological well-being